The impact of sarcopenia on the postoperative outcome in colorectal cancer surgery - Benedek, Zalán; Coroș, Marius Florin (Medicine and Pharmacy Reports, 2023)
Background and aim. Malnutrition-induced sarcopenia predicts poorer clinical outcomes for patients with cancer. Postoperative complications such as wound infection, anastomotic leak (AL), cardiorespiratory events are the most frequent and devastating postoperative complications in colorectal cancer surgery and are frequently associated with malnutrition. Methods. We reviewed the recent available literature to assess the relationship between the patient nutritional status and sarcopenia in colorectal surgery. The PubMed database was searched for publications. The included studies were original articles, prospective and randomized trials, clinical, systematic reviews and meta-analyses. The information was structured in a narrative review form. Results. A simple method to assess malnutrition is to define the presence of sarcopenia (skeletal muscle mass reduction and modified composition) by radiological image analysis. Quantifying the material composition and quality is a novel method in patient-specific therapy. This could be a new perspective in colorectal surgery to reduce postoperative mortality, improve surgical planning, and enhance clinical outcomes. A few recent studies have objectively investigated the presence of sarcopenia in colorectal cancer and its impact on morbidity and mortality, but sometimes the results are contradictory. Conclusion. There is evolving research to find the most appropriate management method , surgeons must be aware of the existence of sarcopenia to identify this risk factor in the occurrence of postoperative complications in colorectal cancer surgery.